Geochemical and structural constraints on the magmatic history of the Chandman Massif of the eastern Mongolian Altay Range, SW Mongolia - Economos,R.C.; Hanzl,P.; Hrdlickova,K.; Burianek,D.; Said,L.-O.; Gerdes,A.; Paterson,S.R. (Journal of Geosciences, 2008)
In the Mongolian Altay range, immediately south of the Bogd fault zone, the Chandman Massif intruded the Chandman Khayrkhan Crystalline Complex to the NE. This complex consists of migmatized biotite gneisses, orthogneisses and amphibolites. To the south, the Massif cuts the chlorite schists and quartzites of the Tugrug Formation. The Massif mainly consists of diorites to granites with rare gabbro bodies interspersed with metamorphic host rock screens, generally of amphibolite with calc-silicate lenses. Granitoids are further categorized based on petrography and whole-rock geochemical data into peraluminous and metaluminous groups. Granites comprise the peraluminous group, and possess high (71-77 wt. %) silica contents and abundant modal K-feldspar. Metaluminous granitoids span a wide range in silica contents, from diorite to granite. Also their feldspars are compositionally variable. Both these granitoid units are of volcanic-arc character and display a calc-alkaline geochemical trend. Granodiorites of the metaluminous group contain widespread planar rhythmic schlieren layering. Metaluminous units slightly predate the intrusion of peraluminous granites, but the two suites are occasionally co-magmatic. The Al-in-hornblende barometric analysis combined with plagioclase thermometry reveals a depth of emplacement of 11.5-13.7 km and magma temperatures of 725-775 ºC. Chandman Khayrkhan metamorphic foliations strike NNW. Magmatic fabrics in the Chandman Massif roughly E-W and subparallel E-W solid-state foliations overprint magmatic foliations. All foliations are moderately to steeply dipping. Fabric analysis shows a discordance of structures to the north and south of a fault that cross-cuts the field area. This fault is interpreted to be related to motion on the Bogd fault. Thus, this area experienced 1) amphibolite-facies metamorphism of the Chandman Khayrkhan Crystalline Complex, 2) exhumation to higher crustal levels, 3) juxtaposition against the greenschist-facies Tugrug Formation, 4) intrusion of the Chandman Massif under tectonic strains that continued through the solidification of plutons, and 5) late block-style rotation related to motion on recent faults. These age and geological constraints identify the Chandman Massif as an intrusion of substantially younger age than the “Caledonian” association into which it was previously placed. It is thus far the only arc-type intrusion in the earliest “Hercynian” age range identified in the Gobi-Altay Terrane. Its metamorphic and magmatic history of migmatization followed by intrusion of metaluminous and peraluminous plutons are similar to those of rocks to the west, in the Tseel Terrane, and may represent its easternmost counterpart. The exact juxtaposition mechanism for metamorphic units of different grade and the formation of schlieren layering in the Chandman Massif granodiorites remain enigmatic.
Keywords: Mongolian Altay; Al-in-hornblende barometry; Gobi-Altay Terrane; magmatism; arcs; granite; Chandman Massif